INTERNATIONAL TAX PLANNING FOCUSING ON THE REDUCTION OF THE TAX BURDEN - Barbosa Marques, Carolina (Revista Gênero e Interdisciplinaridade, 2022)
International tax tax planning is extremely important for companies, as it makes it possible to reduce the tax burden when done well. This article, through a literature review, aimed to discuss the main aspects of international tax planning and its influence on reducing tax burdens. In short, Tax planning is a tool used within the scope of the law, which can be applied through loopholes or other legal systems, in order to reduce the taxpayer’s tax burden as much as possible. It was also noted that tax reduction occurs when the use of international differences in the tax burden results in a reduction of the tax burden in relation to the tax burden in the country of residence. This is achieved by taking advantage of interstate tax differences, differences in international tax systems, and incomplete interstate coordination.